Overview of contents of web pages about public health pest control services - Gámez de la Hoz, Joaquín; Padilla Fortes, Ana (Revista General de Información y Documentación, 2015)
Introduction: Our goal was to know the web contents and examine the technical information pest control services available to users through their webpages. Method: A total of 70 webpages from biocides services in the province of Málaga (Spain) were analyzed. We used 15 evaluation indicators grouped into 5 parameters relating to data of the service provider; information’s reliability and services; accuracy of content and writing style; technical resources and interaction with the users. As test instruments were used sectoral legislation, official records of products and deliveries, standards and technical guides. Results: Companies showed a remarkable degree of awareness with the implementation and use of new technologies. Aspects negative that they can have an impact on the confidence of users, relating to the reliability of the information and deficiencies associated with the description of the services portfolio and credentials of the companies were identified. The integration and use of collaborative platforms 2.0 was poorly developed and squandered. Discussion: It is possible to improve the trust of users intervening in those aspects that affect the reliability of the information provided on the web.
Keywords: Biocides; Documentation; Environmental health; Information society indicators; Internet; Pest control; Public health; Webcasts.